‘How ideas become effective in history’: Max Weber on Confucianism and beyond - Schluchter, Wolfgang (Forum for Inter-American Research, 2020)
Max Weber’s interest in East Asia starts as early as 1898, but it comes to fruition only after 1910. Instead of continuing his essays on ascetic Protestantism, as promised to the public, he embarked on a comparison of world religions, in which he included Confucianism, although he did not regard it as a religion in the strict sense of the term. As a matter of expediency, he used Confucianism, however, as the most pronounced counterexample to ascetic Protestantism, seemingly similar from the outside, but totally different from the inside. So, Confucianism is included in his attempt to provide a sociology and typology of religious rationalism. Confucianism is also used as a backdrop to understand the singularity of the Western development. The sketch, as he calls it, is not meant as a full-fledged analysis of this intellectual and social movement nor of Imperial China at large. Therefore, it is very dangerous to apply Weber’s analysis to the current situation in China (after the “Cultural Revolution” and the one-child policy). I call this the fallacy of misplaced application. This does not rule out, however, using Weber’s methodology and conceptual tools to a certain extent for such an analysis. How this could be done, is shown in the last section of this presentation.
Gesehen am 23.11.2021